Landscapes of Prehistoric Northwestern Sichuan: From Early Agriculture to Pastoralist Lifestyles. (17th February 2018) - d'Alpoim Guedes, Jade; Hein, Anke
ABSTRACT: We describe a preliminary survey of a relatively unknown part of the eastern Himalayas: northwestern Sichuan. This survey revealed that three phases of occupation are represented across the landscape. Large settlements with dense remains characterize the landscape during the Neolithic (3400–2000cal b.c. ). Following a hiatus in occupation, stone-cist graves characterize the region during the Bronze Age (1450–800cal b.c. ). The lack of settlement remains from this period indicates that mobile pastoralism increased in importance. Finally, betweena.d. 500 and 1500, dense scatters of ceramics over a wide altitudinal range correspond to a fragmentation in Tibetan history, when local warlords established themselves in the region. While some changes in occupation and subsistence practices are linked to climate change, others relate to changes in political power. We argue that further survey work is needed to expand our understanding of past land use and the development of pastoralist practices.